Ta mala niesmiertelnosc : sceny widowiska - Gruda, Konrad (Warszawa : Oficyna Wydawnicza Rytm, 1997)
A translation from the German of Konrad Gruda's: Diese kleine Unsterblichkeit, a contemporary media novel.